Applicability of Toronto Clinical Neuropathy Scoring and its Correlation with Diabetic Peripheral Neuropathy: A Prospective Cross-sectional Study - D Udayashankar; Sarah S Premraj; K Mayilananthi; Vishwanath Naragond (Journal of Clinical and Diagnostic Research, 2017)
Introduction: Diabetes is a non-communicable metabolic disorder which is associated with numerous vascular and non-vascular complications. Neuropathy is one of the most important complications which, if not recognized and treated early may result in significant disability and poor quality of life. In a resource poor setting like India, where diagnostic modalities like Nerve Conduction Study (NCS) are expensive for early diagnosis, the present study aimed to evaluate the effectiveness of a simple bed side assessment test, the Toronto Clinical Neuropathy Scoring (TCNS) system in diagnosing Diabetic Peripheral Neuropathy (DPN). Aim: The primary objective was to determine the applicability of Toronto clinical scoring system in DPN diagnosed by NCS in the South Indian population. The secondary objective was to evaluate the correlation between duration of Diabetes Mellitus (DM), HbA1C, diabetic retinopathy and neuropathy with severity of diabetic neuropathy as determined by the TCNS. Materials and Methods: In a prospective cross-sectional study, conducted over a period of 12 months from June 2015 to May 2016 at a tertiary care institute in semi-urban South India, 50 diabetic patients with symptomatic neuropathy were included. All patients were subjected to TCNS and the results were compared with neuropathy confirmed by NCS. Categorical variables were expressed as percentage or proportions. Comparison of normally and abnormally distributed continuous variables were done by independent sample t-test and Mann – Whitney U test respectively. Categorical variables were compared using Chisquare test or Fisher’s exact test. A p-value less than 0.05 was considered statistically significant. Results: The presence of neuropathy by TCNS was confirmed in all cases by NCS. Further the severity of neuropathy as assessed by TCNS was found to correlate well with duration of diabetes, and the presence of diabetic retinopathy and nephropathy. Presence of foot weakness, ataxia and upper limb symptoms also had direct correlation with severity of diabetic neuropathy. Conclusion: TCNS is a sensitive scoring system used to diagnose diabetic neuropathy and can be used as an inexpensive bedside screening tool.